Photosynthetic Capabilities And Responses Of Hard Corals To Turbidity Influence And Thermal Stress - Mubin, Nur Ain Amani Abdul (2018)
It was hypothesized that different species and colonies of corals have different photo-physiological responses to exposure time and elevated temperature. This thesis investigates the effect of 2 hours and 24 hours exposure and elevated seawater temperature on the photo-physiology of hard corals collected from Pulau Kendi, Penang and Pulau Songsong, Kedah. Pulau Kendi and Pulau Songsong are located at the northern region of Peninsular Malaysia, both are known as highly sedimented areas with low-light condition with photosynthetically active radiation (PAR) values of 24.707 ± 1.329 μmol m-2 s-1and 54.267 ± 1.739 μmol m-2 s-1 respectively (measured at 12pm). To investigate the photo-physiology of corals in turbid water from both study sites, an in-situ photo-physiology measurements were conducted using DIVING-Pulse Amplitude Modulated (PAM) fluorometer. Maximum quantum yield (Fv/Fm) values were recorded the highest was found in Porites lutea (0.787 ± 0.034) and Goniastrea aspera (0.730 ± 0.010) from Pulau Kendi and Pulau Songsong respectively. Rapid light curves (RLCs) showed similar trend for all species with light saturation occurring at 2000.00 μmol m-2 s-1. Photosynthetic parameters obtained showed that all species have different photosynthetic activity despite having similar morphology. Turbinaria mesenterina showed the highest α (0.040 ± 0.002) which indicated that plate type coral has better photosynthetic efficiency compared to other morphology type.